2006
DOI: 10.1007/s00049-006-0342-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical defense of the ladybird beetle Epilachna paenulata

Abstract: The defensive chemistry of the ladybird beetle Epilachna paenulata (Coleoptera: Coccinellidae) was characterized as a mixture of piperidine, homotropane and pyrrolidine alkaloids. Whole body extracts of adult beetles contain four major alkaloids: 1-(6-Methyl-2,3,4,5-tetrahydro-pyridin-2-yl)-propan-2-one; 1-(6-methyl-2-piperidyl)-propan-2-one; 9-aza-1-methyl-bicyclo[3.3.1]nonan-3-one and 1-(2´´-hydroxyethyl)-2-(12´-aminotridecyl)-pyrrolidine. Comparative studies of the defensive chemistry of eggs, larvae, pupae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Larvae that had been provoked developed into smaller females than unprovoked larvae. Results of exudate collection from individuals of different ages suggested that there was an age -related variation in the amount of defence fl uid produced and the concentration of alkaloids, in line with what has been described for Epilachna paenulata mentioned above (Camarano et al 2006 ).…”
Section: Production C Ostsupporting
confidence: 85%
See 1 more Smart Citation
“…Larvae that had been provoked developed into smaller females than unprovoked larvae. Results of exudate collection from individuals of different ages suggested that there was an age -related variation in the amount of defence fl uid produced and the concentration of alkaloids, in line with what has been described for Epilachna paenulata mentioned above (Camarano et al 2006 ).…”
Section: Production C Ostsupporting
confidence: 85%
“…Comparisons of the composition of alkaloids in eggs, larvae, pupae and adults showed both qualitative and quantitative differences between the four life stages, and also varied during the adult stage, with optimum content during the oviposition period. Laboratory predation bioassays showed that adults are better protected than larvae and pupae against wolf spiders and, in fi eld tests, the adult alkaloid extract also was deterrent to ants (Camarano et al 2006 ). control females.…”
Section: Production C Ostmentioning
confidence: 99%
“…It was found that these predators relatively rarely attack coleopterans because of their thick and hard cuticle (Nentwig 1986, Nyffeler 1999 ). In the case of Coccinellidae, defensive alkaloids may act as additional protection (Eisner et al 1986 ;Camarano et al 2006 ).…”
Section: Morphological a Nti -P Redator A Daptationsmentioning
confidence: 99%
“…When sensing danger, ladybirds emit poisonous and odious droplets (reflex bleeding). It has been demonstrated that chemical signals of ladybirds can prevent attacks by olfactory orienting predators such as ants (Sloggett, Wood & Majerus, 1998; Pasteels, 2007), spiders (Camarano, Gonzalez & Rossini, 2006), true bugs (HoughGoldstein, Cox & Armstrong, 1996), lacewings (Lucas, 2005), and other ladybirds (Agarwala & Dixon, 1992). The presence of toxic chemicals in ladybirds also represents a potential danger for optically orienting predators such as birds.…”
Section: Introductionmentioning
confidence: 99%